Queen's Park Hotel, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
This postcard shows the front of the Queen's Park Hotel which is located opposite the Queen's Park Savannah, south. Noticeable here is the 1937, five storey, Art Deco renovation at the centre of the building. Guests can be seen on the steps of the hotel and a few taxis are packed on either side of the road.
Colour: Black and white; Style: Portrait; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Hotels--Trinidad and Tobago; Buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Historic hotels--Trinidad and Tobago; [1940]; Cities and towns--Trinidad and Tobago--Port of Spain; Architecture--Trinidad and Tobago; Roads--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Transportation--Trinidad and Tobago; Taxicab industry--Trinidad and Tobago; Taxicabs--Trinidad and Tobago; Men--Trinidad and Tobago; Women--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Roads--Guard fences; Balconies--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)